Irrigation-Intensive Groundwater Modeling of Complex Aquifer Systems Through Integration of Big Geological Data - Vahdat-Aboueshagh, Hamid; Tsai, Frank T.-C.; Bhatta, Dependra; Paudel, Krishna P. (Frontiers in Water, 2021)
This study identifies hydrogeologic characteristics of complex aquifers based on constructing stratigraphic structure with large, non-uniform well log data. The approach was validated through a modeling study of the irrigation-intensive Chicot aquifer system, which is an important Pleistocene-Holocene aquifer of the Coastal Lowland Aquifer System in the southwestern Louisiana. Various well log types were unified into the same data structure, prioritized based on data sources, and interpolated to generate a detailed stratigraphic structure. More than 29,000 well logs were integrated to construct a stratigraphy model of 56 model layers for the Chicot aquifer system. The stratigraphy model revealed interconnections of various sands in the system, where 90% of the model domain is covered by fine-grained sediments. Although the groundwater model estimated a slight groundwater storage gain during 2005-2014 for the entire region, groundwater storage in the agricultural area was depleted. Nevertheless, the quick groundwater storage recovery during the non-irrigation seasons suggests that the Chicot aquifer system is a prolific aquifer system. The groundwater modeling result shows that the gulfward groundwater flow direction prior to pumping has been reversed towards inland pumping areas. The large upward vertical flow from the deeper sands indicates potential saltwater migration from the base of the Chicot aquifer system.